Equity and Artificial Intelligence in Surgical Care: A Comprehensive Review of Current Challenges and Promising Solutions - Ahsan Ahmad; Aftab Tariq; Hafiz Khawar Hussain; Ahmad Yousaf Gill (CV. Multi Kreasi Media, 2023)
The use of artificial intelligence (AI) has become a viable method for improving surgical care equity. In order to better understand the effects of AI in surgical settings, this paper focuses on five key areas: promising AI applications, bias-reduction tactics, and ethical AI implementation, effects on patient outcomes and access to surgical services, and future directions for equitable AI in surgical care. The first part of the article looks at the exciting uses of AI in surgery. It emphasizes how AI technology may boost decision-making, increase surgical precision, and improve patient care routes. Better surgical outcomes, individualised treatment plans, and streamlined procedures can all result from the incorporation of AI algorithms, which will ultimately help patients from a variety of groups. The solutions for reducing bias and fostering equity in AI-enabled surgical care are covered in more detail in the second part. In order to reduce biases, it emphasizes the value of diverse and representative datasets, algorithmic transparency, and fairness metrics. Healthcare disparities can be decreased by proactively addressing bias, and AI-enabled surgical care can help ensure fair outcomes for all patient populations. The final segment is devoted to removing obstacles in the way of deploying moral AI procedures in surgical settings. It places a strong emphasis on the necessity of open governance structures, informed consent procedures, privacy protection, accountability, and ongoing ethical assessment. Accountability is guaranteed through transparent governance systems, which also offer a way to address moral issues and potential biases. The implications of AI for patient outcomes and access to surgical services are covered in the fourth part. It emphasizes how AI technologies have the potential to enhance decision-making, improve surgical results, and streamline patient care routes. It also covers issues with bias, privacy, and ethics that must be taken into account to enable responsible and fair implementation. The fifth segment examines potential future directions and surgical care opportunities for egalitarian AI. Strong data infrastructure, advances in deep learning and machine learning, explainable AI, AI-driven surgical automation, tackling health disparities, and the creation of ethical and legal frameworks are some of the themes it highlights. These regions have enormous opportunity to improve patient outcomes and advance fair access to surgical care. Enhancing equity is made possible by the incorporation of AI in surgical care. Healthcare organizations can enhance surgical results, lower inequities, and guarantee equitable access to surgical services by utilizing AI technologies. To be responsible and equitable, a deployment must address bias, adhere to ethical standards, and take into account how AI is developing. To maximize the advantages of AI in surgical care while advancing equity and patient-centered care, future research and collaboration are crucial.